Comparison of Intratympanic and Systemic Steroid Therapy as Primary Treatments for Idiopathic Sudden Sensorial Hearing Loss - Fuji, Sayaka; Takeuchi, Ayako; Kariya, Akifumi; Akisada, Naoki; Koyama, Takahisa; Fujisawa, Iku; Hamada, Koji; Ishihara, Hisashi; Akagi, Seiko (International Journal of Practical Otolaryngology, 2023)
Recently, intratympanic steroid (ITS) therapy has been used as a primary or salvage treatment for idiopathic sudden sensorineural hearing loss (ISSHL). In the present study, we retrospectively compared the efficacies of ITS and systemic steroid (SS) therapies as primary treatments for ISSHL. This study included 112 patients treated for ISSHL at our hospital, of which 44 received ITS therapy and 68 received SS therapy. Regarding patient background characteristics, the mean age (76 vs. 65 years, p < 0.0001) and percentage of patients with diabetes mellitus (55 vs. 18%, p < 0.0001) were significantly higher in the ITS group than in the SS group, whereas the rate of prior steroid use was lower in the ITS group than in the SS group (9 vs. 31%, p = 0.0068). After 3 weeks, the treatment response was cure, marked recovery, recovery, and no change in 11, 9, 8, and 16 patients in the ITS group and 32, 11, 5, and 20 patients in the SS group, respectively. Accordingly, the SS group was found to have a significantly higher cure rate than the ITS group (47 vs. 25%, p = 0.0191), with similar findings after propensity score matching (48 vs. 22%, p = 0.0461). Therefore, SS therapy is recommended as a primary treatment for ISSHL in patients who are not old or at a high risk of SS therapy-associated complications.
Keywords: idiopathic sudden sensorineural hearing loss; intratympanic steroid therapy; primary treatment